Pengembangan Sistem Informasi BSC Kinerja Redaksi di Radar Sampit - Linda Sutriani; Slamet Riyadi (KLIK: Kajian Ilmiah Informatika dan Komputer, 2020)
Performance is a result achieved by a person in carrying out the tasks assigned to him in terms of quality and quantity in work. To improve the performance of journalists, it is necessary to make efforts so that journalists still have high morale in carrying out their duties. The Balance Scorecard can be used more than just as a measurement system but also to communicate new strategies and align the company to those new strategies. Currently, in the arena of increasingly fierce and competitive business competition, companies are required to sharpen their direction and strategy in an integrated manner so that the company's vision and mission can be realized. However, the process of transforming the company's vision into reality is not easy to implement, it requires a comprehensive performance system that is useful for all elements in the company with the aim of translating the vision and mission into a clear program so that it can be carried out effectively. The Balance Scorecard system is an interesting solution to be applied in an era of continuous transformation, because the system as a whole sees four perspectives, namely: a financial perspective, a customer perspective, an internal business process perspective, and a growth and learning perspective. As a measurement system related to strategy, the four perspectives must present linkages and synergistic relationships as a strategic unit in an effort to achieve long-term goals.